Influence of lower extremity rotation on knee kinematics in single-leg landing. (November 2022) - Shinde, Takuto; Saito, A.; Okada, K.; Wakasa, M.; Kimoto, M.; Kamada, T.; Shibata, K.; Okura, K.; Sato, H.; Takahashi, Y.
Abstract: Objectives: Although the rotation of lower extremities has gained increasing recognition as a risk factor for anterior cruciate ligament (ACL) injury. This study clarified the influence of lower extremity rotation on the knee during single-leg landing. Design and Setting: We recruited 30 students to perform single-leg landing from a height of 30 cm with their lower extremities in neutral, and externally and internally rotated. The knee abduction, flexion angles, and abduction angular velocity were measured. Furthermore, the abduction angle was analyzed at knee flexion angles of 15°, 20°, 25°, and 30° and compared among the three conditions using a repeated measures analysis of variance with Bonferroni post hoc tests. Results: The maximum abduction angle was significantly greater when internally rotated than in the neutral. The maximum abduction angular velocity was significantly greater in the internally rotated compared to in the neutral. Finally, the abduction angle at a knee flexion angle of 30° was significantly greater when internally rotated compared to in the neutral. Conclusion: Rotation of the lower extremities affects knee kinematics, and landing on a knee that is internally rotated may increase the risk of ACL injury. Highlights: We studied the impact of lower extremity rotation on the knee in single-leg landing. The maximum valgus angle and angular velocity were greater when internally rotated than in the neutral. Rotation of the lower extremities affects knee kinematics. Landing on an internally rotated knee may increase risk of ACL injury.